Methods of overvoltage limitation in modern dc semiconductor switching apparatus and their calculation - Soskov, Anatoly; Sabalaeva, Natalia; Glebova, Marina; Forkun, Yana (Eastern-European Journal of Enterprise Technologies, 2016)
The study considers switching surges at semiconductor switches of semiconductor devices of the direct current at the time of switching electric circuits; such surges occur due to the energy accumulated in the inductive elements of the mains at the load disconnection. As the cost of power semiconductor devices is determined not only by the voltage that they are able to handle but also by the class of the device that determines the amount of the blocked voltage, an important task is to use special measures to reduce these surges down to levels that are close to the network parameters. The aim of this study was to develop a methodology for calculating the parameters of a regulator of switching surges on the basis of a series of parallel-connected energy-intensive varistors used in semiconductor devices of the direct current. On the basis of studying the transient processes that occur in such surge restrictors of voltage in semiconductor devices of the direct current at load switching, analytical expressions have been developed for calculating the basic parameters of the voltage regulator. As a result, an engineering method has been devised for calculating the parameters of varistor surge regulators in hybrid and contactless semiconductor devices of the direct current at a given level of surge admissible for this class of devices. The research findings facilitate high accuracy at a small amount of time in choosing fully controlled semiconductor devices with regard to the current and voltage when designing modern switching semiconductor apparatus that work with the direct current; this helps solve the basic tasks of planning. The suggested voltage regulator for semiconductor switching apparatus of the direct current effectively limits switching surges in the circuits of power semiconductor devices to below 2.5 Unom. It significantly surpasses such parameters as the dimensions, weight and cost of resistive-capacitive surge limiters previously used in semiconductor contactors. Moreover, it can reduce the class level of fully controlled power semiconductor devices that are used in semiconductor switches of such apparatus.